Sistem Ekonomi Pancasila Di Negara Hukum Indonesia Dalam Menjamin Hak Warganegara Atas Pembaharuan Melalui Affiliate Tiktok Shop - Niken Aulia Kusumawati; Yukova Miska Athira ; Windi Edriani Ningsih; Mustaqim Mustaqim (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Indonesia, as a country with the philosophical foundation of Pancasila, embraces the Pancasila Economic System that prioritizes social values, justice, and people's welfare. In its development, the Indonesian economy has undergone significant transformation, especially with the adoption of digital technology. One of the recent phenomena that characterizes this change is the emergence of online business models, including Affiliate TikTok Shop. As the foundation of the state, Pancasila affirms the human rights of citizens, especially the freedom to pursue economic prosperity and progress. It is hoped that in this situation, the Pancasila Economic System will serve as the foundation for implementing economic changes that advance the welfare of all citizens. Therefore, a thorough examination of the implementation of the Pancasila Economic System is needed to protect the rights of citizens through Affiliate TikTok Shop. The TikTok Shop Affiliate business model, which combines a digital business component with affiliate network marketing, has developed into an important component in the ecosystem that supports the digital economy. An important topic is how the Pancasila Economic System responds and adapts to these processes. Measuring how well the ideals of Pancasila and the rights of the people are upheld in the era of digital economic change will become easier with an understanding of the functioning of the Pancasila Economic System in TikTok Shop Affiliation. In an effort to explore the possibility of economic rejuvenation, this research becomes relevant when analyzing the interactions between the Pancasila Economic System, the Indonesian Rule of Law, and the TikTok Shop Affiliation. By gaining a deeper understanding of these interactions, strategies that facilitate the establishment of a just and inclusive digital economy in Indonesia can be developed.